2015
DOI: 10.1021/acsami.5b04780
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Mesoporous Dendrimer-Coated Titanium Dioxide: Insight on the Role of the Surface–Interface Composition and the Framework Crystallinity

Abstract: Hitherto, the field of nanomedicine has been overwhelmingly dominated by the use of mesoporous organosilicas compared to their metal oxide congeners. Despite their remarkable reactivity, titanium oxide-based materials have been seldom evaluated and little knowledge has been gained with respect to their "structure-biological activity" relationship. Herein, a fruitful association of phosphorus dendrimers (both "ammonium-terminated" and "phosphonate-terminated") and titanium dioxide has been performed by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
5
19
0
Order By: Relevance
“…It can be observed that although a high number of studies have been reported on cationic peptide Ds, dendrimers such as PAMAM Ds and peptide Ds have been developed throughout the decade. On the contrary, other structures, such as ammonium-terminated Ds (AT-Ds), including AT phosphorous and carbosilane Ds [ 59 , 60 ], attracted the interest of scientists only after 2015. Other Ds, such as PPI Ds, after initial consideration, were neglected, while PEI-Ds and organometallic Ds (OM-Ds), were taken into consideration only marginally.…”
Section: Cationic Antibacterial Dendrimers (Cads)mentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that although a high number of studies have been reported on cationic peptide Ds, dendrimers such as PAMAM Ds and peptide Ds have been developed throughout the decade. On the contrary, other structures, such as ammonium-terminated Ds (AT-Ds), including AT phosphorous and carbosilane Ds [ 59 , 60 ], attracted the interest of scientists only after 2015. Other Ds, such as PPI Ds, after initial consideration, were neglected, while PEI-Ds and organometallic Ds (OM-Ds), were taken into consideration only marginally.…”
Section: Cationic Antibacterial Dendrimers (Cads)mentioning
confidence: 99%
“…By performing a sol-gel process, the fruitful association of a fourth-generation phosphorus dendrimer, peripherally modified with quaternized ethylene diamine and titanium dioxide (TiO 2 ), was realized by Milowska et al (2015) together with other three ones [ 59 ]. The hybrid mesoporous dendrimer-coated TiO 2 obtained showed to be nanosized, in a crystalline and to possess a surface mimicking that one of PEI-Ds.…”
Section: Cationic Antibacterial Dendrimers (Cads)mentioning
confidence: 99%
See 1 more Smart Citation
“…The photovoltaic cells based on titanium dioxide are wellknown for its high-efficiency in dye-sensitized solar cells since Grätzel and co-workers incorporated dinitrogenated ruthenium (II) complexes onto the TiO 2 surface [1][2][3]. TiO 2 surfaces as rutile or anatase-like forms have a skeleton of titanium and oxygen atoms spatially distributed [4,5] providing a high number of Ti-OH groups on the solid surface [6,7], which allows linking of organometallic compounds and organic chains for the preparation of hybrid materials [8][9][10]. On the other hand, the controlled manufacture of dye-sensitized TiO 2 structures at the nanometric scale allows either promote or suppress the recombination of electron and hole pairs upon UV-visible light excitation, conferring to TiO 2 -based materials an increasing interest within renewable energy and environment fields as well as in nanotechnology [1][2][3][4][5]8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatible poly(ethylene glycol) (PEG) can also be modified on dendrimers to decrease the cytotoxicity of dendrimers and improve their biodistribution behavior [ 26 , 27 ]. Since the combination of organic and inorganic nanohybrids has been demonstrated to have a synergistic performance [ 28 , 29 , 30 ], it is plausible to hypothesize that the modification of PAMAM dendrimers on the surface of LAP nanodisks would improve the performance of a LAP-based drug delivery system through providing additional drug loading capacity and endowing LAP nanodisks with active functional groups for targeting modification.…”
Section: Introductionmentioning
confidence: 99%